The morphology and aspects of the behaviour of Eremnus cerealis Marshall (Coleoptera: Curculionidae) - Van den Berg, H. C (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1970.